IMPLEMENTASI PEMBELAJARAN TEMATIK PADA SISWA KELAS III MI AL HIDAYAH KASEMBON BULULAWANG MALANG - Aminatus Sholiha; Muhammad Hanief; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Thematic learning is learning that explains the thmes that have been determined according to the curiculum and implemented for chidern who are in the early age range (7-11) or more, are in concrete operations. Childern at this age have a tendency of elements simultaneously, begin to think operationally. This qualiative uses a reseach approach and the type is a study case. Conducted att MI Al-Hidayah Kasembon Bululawang with grade 3 students as objects. The results of this study are first that the thematic learning planning for third grade students at MI Al-Hidayah Kasembon Bululawang Malang goes through several stages, namely the teacher prepares a learning implementation plan (RPP) which has been aligned with the syllabus that has been determined. And teachers prepare learning media as a means of supporting thematic learning to be more effective. Second, the implementation of thematic learning in class III students of MI Al-Hidayah Kasembon Bululawang Malang is that teacher has carried out thematic learning in accordance with the lesson plans and syllabus that have been determined, supported by effective learning media. The evaluation system carried out in thematic learning in class III MI Al-Hidayah Bululawang is in the form of remedial.